Clinical, structural, biochemical and X‐ray crystallographic correlates of pathogenicity for variants in the C‐propeptide region of the COL3A1 gene. (5th April 2015) - Stembridge, Natasha S.; Vandersteen, Anthony M.; Ghali, Neeti; Sawle, Philip; Nesbitt, Mandy; Pollitt, Rebecca C.; Ferguson, David J. P.; Holden, Simon; Elmslie, Frances; Henderson, Alex; Hulmes, David J. S.; Pope, F.Michael
<x xml:space="preserve">Abstract</x> Vascular Ehlers–Danlos syndrome (vEDS) is a heritable disorder of connective tissue caused by pathological variants in the COL3A1 gene, which encodes the α1 chain of type III collagen. Type III collagen is a major component of skin, arterial walls, and the gastrointestinal tract. Collagen III protein deficiency manifests as an increased risk of rupture, perforation, and dissection of these structures. The most disruptive gene variants affect the collagen helix via glycine substitutions or splice donor site mutations. The C‐propeptide region of COL3A1 includes exons 49–52 and has a crucial role in initiating the C‐terminal assembly of procollagen monomers in the early stages of collagen biosynthesis. Nineteen COL3A1 variants have previously been reported in these exons, of which four were associated with a severe vEDS phenotype. We identified two novel C‐propeptide missense variants; p.Pro1440Leu, p.Arg1432Leu, and a non‐stop mutation, c.4400A > T, p. (*1467Leuext*45). These variants produce variable phenotypes ranging from obvious acrogeria to classical or hypermobile EDS. A previously reported variant p.Lys1313Arg is of unknown clinical significance but likely benign, based on this study. Assigning disease pathogenicity remains complex, clinical phenotyping and crystal structure evidence being crucial. We briefly compare reported phenotypes for patients with missense variants in the C‐propeptide domain for other human collagen disorders including COL1A1 and COL1A2 (osteogenesis imperfecta). © 2015 Wiley Periodicals, Inc.